Surgical and cell therapy in critical limb ischemia: Current evidence and rationale for combined treatment with special focus on diabetic patients - Del Foco, Ottorino; Bencomo-Hernandez, Antonio; Castillo-Aleman, Yandy; Sanna, Pierdanilo; Benedetti, Stefano; Dassen, Enrico (Journal of Diabetes and Endocrine Practice, 2021)
Critical limb ischemia (CLI) is considered the end-stage of peripheral arterial disease, with a prevalence between 2% and 4% in the general population and more than 15% in older adults. One-year major amputation rate can reach 30%, and diabetic patients are five times more likely to develop CLI than nondiabetics. The vascular damage and the complexity in the anatomical extension of the lesions are also worse in people with diabetes with poorer outcomes after vascularization attempts. Following the classifications suggested by international guidelines, we can define the presence of CLI and have a precise evaluation of the amputation risk and the best revascularization procedure for the patient. Nowadays, new endovascular techniques and devices make it possible to treat tibial vessels and even arteries below the ankle with promising initial results. Nevertheless, the re-occlusions rate and the need to re-do treatments at 1 year remain between 30% and 50%. The disease progression and hyperplasia can because it. However, the damage at the microcirculatory level can also lead to a decrease in tissue runoff and an increase in peripheral resistance, which determine the revascularization failure. In the last 20 years, several trials have been designed to avoid amputation in patients with no surgical options. The aim is to find a valid cellular base therapy to create a new vessel web in the ischemic tissue based on the angiogenetic power that stem cells have already demonstrated in vitro and animal studies. Different types of cells have been tested with different concentrations and administration routes with promising results. CD34+ Mononuclear cells, Mesenchymal stem cells, growth factors have demonstrated their contribution to the neo-angiogenesis in ischemic areas. At Abu Dhabi Stem Cells Center, we created a cellular cocktail as an adjunct treatment to surgical revascularization. We think that acting at the microcirculatory and immunological level. We may reduce postsurgery hyperplasia and increase tissue perfusion, ultimately prolonging the patency of revascularization procedures.
Keywords: Critical limb ischemia; endovascular; major amputation; mesenchymal stem cells; peripheral arterial disease; surgical revascularization